The Role of the Madukismo Factory in 1955-1958 in the Economy and Industrialization in Yogyakarta: Peran Pabrik Madukismo Tahun 1955-1958 dalam Perekonomian dan Industrialisasi di Yogyakarta - nurul ismi lestari; Rhoma Dwi Aria Yuliantri; arfaton; Mhd Asrian Syah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the role of the Madukismo Sugar Factory in the period (1955–1958) in post-war industrial and social reconstruction in Yogyakarta. Using historical methods that include interviews, archival studies, and field observations, this study highlights how Madukismo played a strategic role in absorbing labor and reviving the industrial sector that was affected by the economic crisis during the malaise. The establishment of this factory was an initiative of Sultan Hamengkubuwono IX in response to the high unemployment rate due to the closure of a number of sugar factories since the previous government. From the results of the research, it can be seen that Madukismo is not only a symbol of local economic recovery, but also contributes to shaping new post-colonial social dynamics. Until now, the Madukismo Sugar Factory remains the only sugar factory still operating in the Yogyakarta area.